2014
DOI: 10.1371/journal.pone.0088656
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Aldehyde Dehydrogenases-2 (ALDH2) Glu487Lys Polymorphism and Colorectal Cancer Risk

Abstract: A number of studies have explored the association of the aldehyde dehydrogenases-2 (ALDH2) Glu487Lys polymorphism and risk of colorectal cancer; however, the results are inconsistent. We performed this meta-analysis to clarify this issue using all the available evidence. Relevant studies were retrieved by searching PubMed. Eleven case-control studies were included in the meta-analysis, representing 2909 cases and 4903 controls. The pooled results based on all included studies showed a decreased colorectal canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
1
8
1
Order By: Relevance
“…Nonetheless, weak associations and study limitations prevent sweeping conclusions regarding the role(s) of ALDH2*2 inheritance in cancer risk. For example, in a meta-analysis of colorectal cancer (CRC) risk and the ALDH2 genotype, the ALDH2*2 allele was unexpectedly found to be protective of CRC [51]. The authors admit, however, that stratification according to drinking status was impossible due to inconsistencies in data collection among studies.…”
Section: Diseases Associated With the Inheritance Of Aldh2*2mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, weak associations and study limitations prevent sweeping conclusions regarding the role(s) of ALDH2*2 inheritance in cancer risk. For example, in a meta-analysis of colorectal cancer (CRC) risk and the ALDH2 genotype, the ALDH2*2 allele was unexpectedly found to be protective of CRC [51]. The authors admit, however, that stratification according to drinking status was impossible due to inconsistencies in data collection among studies.…”
Section: Diseases Associated With the Inheritance Of Aldh2*2mentioning
confidence: 99%
“…The presence of an ALDH2*2 allele by itself is not causally associated with hypertension, rather consumption of alcohol in combination in individuals with the low activity variant which leads to an increase in acetaldehyde concentrations and in aids in the rapid diffusion of aldehydes across cellular membranes is causally associated with adverse physiological issues [1]. Those who express the wild type enzyme are less likely to develop disease from complications stemming from a decreased metabolic rate [28,42,48,50,51,69]. ALDH2*2 and disease unrelated to alcohol consumption: Ischemia occurs when blood flow to a certain tissue system is decreased, which can ultimately damage the tissue.…”
Section: Diseases Associated With the Inheritance Of Aldh2*2mentioning
confidence: 99%
“…Furthermore, when we excluded the studies that were not in HWE or the P HWE values were not available, interestingly, we found the effect of variant allele (504Lys) on colorectal cancer was contrary to that on UADT cancer. Recently, Zhao et al [ 9 ] had reported a similar result and put forward a possible explanation that the unpleasant symptoms resulting from high blood acetaldehyde levels after alcohol consumption may prevent the individuals with the variant allele (504Lys) from consuming alcohol and may keep them from developing alcoholism thus they have much lower chance to expose to the carcinogen acetaldehyde. However, as we could not perform subgroup analysis according to drinkers and non-drinkers to clarify the alcohol-genotype interaction, it is not possible to know whether the role of Lys+ genotypes is protective or not.…”
Section: Discussionmentioning
confidence: 88%
“…In a meta-analysis by Yang et al [ 8 ], ALDH2 504Lys allele was found to increase the risk of esophageal cancer at all levels of exposure to ethanol and acetaldehyde after drinking. On contrary, another meta-analysis by Zhao et al [ 9 ] showed reduced risk for colorectal cancer associated with ALDH2 504lys allele carriers. Considering the contradictory results of the previous studies on ALDH2 Glu504Lys polymorphism with different cancers, we conducted the present meta-analysis to evaluate the relation of ALDH2 Glu504Lys polymorphism with the overall cancer risk.…”
Section: Introductionmentioning
confidence: 95%
“…The studies on the association of the ALDH2 Glu504Lys SNP with the risk of colorectal cancer have given inconsistent results. Two recent meta-analyses indicate that ALDH2 Glu504Lys SNP may be associated with a decreased risk of colorectal cancer [ 67 , 68 ]. No significant impact of Glu504Lys SNP of ALDH2 gene on the risk of hepatocellular carcinoma [ 69 ] and breast cancer has been found in East Asian populations [ 70 , 71 ].…”
Section: Glu504lys Snp Of Aldh2 Gene and The Rimentioning
confidence: 99%